2003
DOI: 10.1203/01.pdr.0000088071.30873.da
|View full text |Cite
|
Sign up to set email alerts
|

CBF Reactivity in Hypotensive and Normotensive Preterm Infants

Abstract: Perinatal distress in the preterm neonate, and the consequent loss of cerebrovascular autoregulation, has been implicated in the pathogenesis of neonatal cerebral lesions. A component of this distress is thought to be hypotension. We examined the autoregulatory capacity of hypotensive and normotensive infants using the 133 Xe technique to measure cerebral blood flow. Global CBF was measured during only normotension in 5 infants, and during both hypotension and normotension in 11 infants. All the infants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 43 publications
6
38
2
Order By: Relevance
“…Xenon, a rare gas, has NMDA antagonist properties 24 and is the only known NMDA antagonist gas that can provide a surgical plane of anesthesia at normobaric pressure. reportedly, xenon is safe for anesthetic use in human neonates 25 and does not cause teratogenic effects in infant rats, as has been reported following isoflurane anesthesia. 26 Very recently, Ma et al 27 reported that xenon, when administered together with isoflurane, reduced the neuroapoptotic response to isoflurane, and xenon, by itself, was not neurotoxic.…”
Section: Conclusion : Nous Concluons Que Le Xénon Dans Le Cerveau Dementioning
confidence: 57%
See 1 more Smart Citation
“…Xenon, a rare gas, has NMDA antagonist properties 24 and is the only known NMDA antagonist gas that can provide a surgical plane of anesthesia at normobaric pressure. reportedly, xenon is safe for anesthetic use in human neonates 25 and does not cause teratogenic effects in infant rats, as has been reported following isoflurane anesthesia. 26 Very recently, Ma et al 27 reported that xenon, when administered together with isoflurane, reduced the neuroapoptotic response to isoflurane, and xenon, by itself, was not neurotoxic.…”
Section: Conclusion : Nous Concluons Que Le Xénon Dans Le Cerveau Dementioning
confidence: 57%
“…Xenon is an effective general anesthetic, when applied at 70% of one atmosphere in humans 24 , and has been used safely for anesthetic or radiological applications in human neonates. 25 Additional advantages in human anesthesia include; ease of administration, rapid onset of action, and rapid recovery. 29,30 Since xenon is exceedingly scarce, difficult to extract in large quantities, and, consequently, very costly, progress in making it commercially available as a general anesthetic has been impeded.…”
Section: Discussionmentioning
confidence: 99%
“…Experience was initially gained by data from animal models like preterm lambs [11,12]. Early techniques that were used to study static autoregulation in preterm infants are the xenon clearance ( 133 Xe) technique or the oxyhemoglobin (HbO 2 ) method by NIRS [13][14][15].…”
Section: Concepts Of Static and Dynamic Autoregulationmentioning
confidence: 99%
“…Their letter raises a number of points primarily concerning the methodology of our study (1). The first question they raise is how CO 2 reactivity was examined.…”
mentioning
confidence: 99%
“…The first question they raise is how CO 2 reactivity was examined. The multiple-regression model used paired values of blood pressure and PaCO 2 measured contemporaneously with CBF measurements (1). In this way, we hoped to determine the individual effects of these predictor variables on our outcome variable (CBF).…”
mentioning
confidence: 99%